Expression of fibroblast growth factor receptor family members is associated with prognosis in early stage cervical cancer patients. Issue 1 (December 2016) - Choi, Chel; Chung, Joon-Yong; Kim, Jae-Hoon; Kim, Byoung-Gie; Hewitt, Stephen
Abstract Background The oncogenic role of the fibroblast growth factor receptor (FGFR) has been recognized in a number of different cancer types. However, the prognostic significance of FGFRs has not been elucidated yet in cervical cancer. In the present study, we investigate the expression of FGFRs and their prognostic value in cervical cancer patients. Methods FGFR1, FGFR2, FGFR3, and FGFR4 expression was determined by immunohistochemistry in conjunction with quantitative digital image analysis of 336 formalin-fixed, paraffin-embedded cervical cancer tissues and 61 normal cervical tissues, as well as NCI60 cell microarray. Subsequently, the association between clinicopathological characteristics and patient survival was assessed. Results FGFRs proteins were differentially expressed in the NCI60 cell line panel and showed considerable correlation between protein and mRNA expression. The expression of FGFR1, FGFR2, and FGFR4 were higher in cancer tissues than in normal tissues, whereas the expression of FGFR3 was higher in normal tissues. FGFR1 was highly expressed in adeno-/adenosquamous carcinoma (P  = 0.020), while FGFR2, FGFR3, and FGFR4 expression were more prominent in squamous cell carcinoma (P  < 0.001, P  < 0.001, andP  = 0.020, respectively). FGFR2 expression was significantly higher in small sized tumors (P  = 0.020). Additionally, high FGFR2 and FGFR4 were correlated with negative lymph node metastasis (P  = 0.048 andP  = 0.040, respectively). FGFR1, FGFR2, and FGFR3 were highly expressed in tumors without parametrial involvement (P  = 0.030, P  = 0.005, andP  = 0.010, respectively). In survival analysis, high expressions of FGFR2, FGFR3, and FGFR4 was associated with longer disease-free survival (P  = 0.006, P  = 0.035, P  = 0.001, respectively) and overall survival (P  = 0.003, P  = 0.002, P  = 0.003, respectively). Notably, the co-expression of all three FGFRs was significantly associated with favorable disease-free survival (P  < 0.001) and overall survival (P  < 0.001), compared to the negative expressions of the three FGFRs. The prognostic significance persisted in the cox regression analysis. Conclusions The frequent expression of members of the FGFR family in cervical cancer suggests they may have prognostic and therapeutic relevance.